INFORMATIONAL ASPECTS OF EMAIL CORRESPONDENCE (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This article explores the informational and communicative aspects of email correspondence within the context of modern information technology. It highlights the transformative role of the Internet as a global medium that integrates traditional and innovative communication methods, fostering a new cultural paradigm. Email, as a prevalent form of electronic communication, blends elements of traditional letters with digital-specific features, emphasizing conciseness, interactivity, and unique structural conventions. It also addresses both the advantages, such as enhanced cognitive practices, and the drawbacks, including reduced social interaction, of Internet communication. Overall, the text underscores email’s significance as a dynamic tool for personal and professional correspondence in the digital age.